2017
DOI: 10.1016/j.fertnstert.2017.07.1053
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after endometrial receptivity array in an infertile population

Abstract: or live birth rates compared with non-injury to the endometrium. Furthermore, endometrial injury in the proliferation phase results in the same effects on the clinical outcomes as the luteal phase. References: 1. Relji M, Knez J, Kova V, Kova B. Endometrial injury, the quality of embryos, and blastocyst transfer are the most important prognostic factors for in vitro fertilization success after previous repeated unsuccessful attempts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The detailed characteristics of the included studies, such as the study design, country, year, patient characteristic, sample size, mean age, and primary outcome, are shown in Table 1 (26)(27)(28)(29)(30)(31)(32)(33). In general, the 17 studies (4 RCTs and 13 cohort studies) included data from 7,052 patients who underwent PET and standard embryo transfer (SET).…”
Section: Description Of the Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed characteristics of the included studies, such as the study design, country, year, patient characteristic, sample size, mean age, and primary outcome, are shown in Table 1 (26)(27)(28)(29)(30)(31)(32)(33). In general, the 17 studies (4 RCTs and 13 cohort studies) included data from 7,052 patients who underwent PET and standard embryo transfer (SET).…”
Section: Description Of the Selected Studiesmentioning
confidence: 99%
“…However, the remaining 2 RCTs still had a high risk of bias because of the incomplete data outcomes and lack of selective reporting (16,27). Figure 6 shows the bias assessment score of the 13 cohort studies (9,10,12,17,19,22,23,28,29,(31)(32)(33). Overall, no study reached the maximum score.…”
Section: Quality Assessment Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular methods simultaneously analyzing hundreds of genes appeared likely at one time to become the new standard, offering new ways of predicting the implantation window (1). In addition to the high cost of the endometrial receptivity array and its complexity, however, further studies showed that performing this test in a mock cycle before an embryo transfer did not improve the ongoing pregnancy rate in patients who had a good prognosis (2,3).…”
mentioning
confidence: 99%
“…7,10,11 However, the standpoint of ERA effectiveness in clinical practice is contradictory. [12][13][14] Displaced and pathological windows of implantation can contribute independently or collectively to implantation failure, 15 which might explain the contradictory results of ERA in clinical practice.…”
Section: Introductionmentioning
confidence: 99%